Students’ Voice: A Need Analysis on Teaching and Learning English at Islamic University - Alfian Alfian (IJET (Indonesian Journal of English Teaching), 2019)
This paper provides a detailed description of the need analysis for designing English teaching and learning activities for non-English major learners. This case study research highlights the need analysis based on the interview and survey data. It was found that speaking and developing vocabulary are the most important language skills and component to be improved. The result also indicated that various activities should be implemented in the classroom, such as a game, pair works, and group discussion and presentation. Furthermore, improving 4 language skills and vocabulary were the target in learning English. This study is crucially important for the process of teaching and learning English and for designing curriculum and course delivery of English for non-majoring students.